(untitled) (Conference Zone, 2022)
This article states that a person, a citizen must have legal awareness, legal culture, legal literacy in order to fully understand and exercise their rights, freedoms and obligations, to know the rights and obligations assigned to him. It is also revealed that the rule of law in society is strengthened by legal culture.